ChemInform Abstract: Metal‐Free and Recyclable Route to Synthesize Polysubstituted Olefins via C—C Bond Construction from Direct Dehydrative Coupling of Alcohols or Alkenes with Alcohols Catalyzed by Sulfonic Acid‐Functionalized Ionic Liquids. Issue 7 (29th January 2015) - Han, Feng; Yang, Lei; Li, Zhen; Zhao, Yingwei; Xia, Chungu
Abstract Both title reactions can be performed on gram‐scale.